2014
DOI: 10.4319/lo.2014.59.5.1510
|View full text |Cite
|
Sign up to set email alerts
|

Community succession in hydrothermal vent habitats of the Eastern Lau Spreading Center and Valu Fa Ridge, Tonga

Abstract: Patterns of succession in Lau Basin hydrothermal vent communities determined with high-resolution imagery and in situ physico-chemical data collected over 4 yr and analyzed within a Geographic Information System show that Alviniconcha snails are a pioneering group, the snail Ifremeria nautilei is a mid-successional species, and the heat-intolerant mussel Bathymodiolus brevior dominates when venting declines. The associated fauna also changes as communities progress through the successional stages, and eventual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 82 publications
7
58
0
Order By: Relevance
“…We imaged the edifices with a forward-mounted camera and made spatially explicit in situ thermal measurements using a temperature probe and the ROV manipulators. Details on the hardware used before 2016 are available in Podowski et al (2010) and Sen et al (2014). During the 2016 expedition, we used an add-on 18-megapixel Canon EOS Rebel T5i digital still camera with a 20 mm Canon lens and the ROPOS high-temperature probe.…”
Section: Deep-sea Expeditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We imaged the edifices with a forward-mounted camera and made spatially explicit in situ thermal measurements using a temperature probe and the ROV manipulators. Details on the hardware used before 2016 are available in Podowski et al (2010) and Sen et al (2014). During the 2016 expedition, we used an add-on 18-megapixel Canon EOS Rebel T5i digital still camera with a 20 mm Canon lens and the ROPOS high-temperature probe.…”
Section: Deep-sea Expeditionsmentioning
confidence: 99%
“…Long-term time-series have been achieved at only a handful of the better-known sites, the majority of which are on medium to fast spreading rate mid-ocean ridges (≥55 mm·year −1 ), such as the Galapagos Rift, the East Pacific Rise, and the Juan de Fuca Ridge (Glover et al, 2010;Beaulieu, 2015). Based on these studies, hydrothermal vents are widely considered to be dynamic, ephemeral habitats (Goldfarb et al, 1983;Chevaldonné et al, 1991;Haymon et al, 1993;Sarrazin et al, 1997;Tunnicliffe et al, 1997;Shank et al, 1998;Johnson et al, 2000;Mullineaux et al, 2003;Cowen et al, 2007;Sen et al, 2014). However, the long-term natural variability of back-arc basin hydrothermal vents is largely unstudied (Boschen et al, 2013;Levin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At Juan de Fuca Ridge, directed changes in community composition from polychaetes (Paralvinella sulfincola and P. palmiformis) to limpets (Lepetodrilus fucensis) to tubeworms (Ridgeia piscesae) over 4 years were related to both changes in fluid flow and associated interactions, appearing to follow a dynamic succession model that allows reversal with changes in fluid flow (Sarrazin et al, 1997). Non-vent endemic deep-sea species appeared in patches where venting subsided (Podowski et al, 2010;Sen et al, 2014).…”
Section: Regional and Local Influences On Successionmentioning
confidence: 99%
“…While succession of large animals at vents is relatively well observed (Sen et al 2014), we know much less on the associated meiofauna and, in particular, on nematodes (Gollner et al 2013). A study on mussel beds of different ages (4 to >20 years) showed that nematodes were less abundant and diverse at younger sites (Copley et al 2007).…”
Section: Introductionmentioning
confidence: 99%